Recognition by natural killer cells of N6‐isopentenyladenosine‐treated human glioma cell lines. Issue 1 (21st September 2017) - Ciaglia, Elena; Laezza, Chiara; Abate, Mario; Pisanti, Simona; Ranieri, Roberta; D'alessandro, Alba; Picardi, Paola; Gazzerro, Patrizia; Bifulco, Maurizio
Abstract : Cancer cell stress induced by cytotoxic agents promotes antitumor immune response. Here, we observed that N6‐isopentenyladenosine (iPA), an isoprenoid modified adenosine with a well established anticancer activity, was able to induce a significant upregulation of cell surface expression of natural killer (NK) cell activating receptor NK Group 2 member D (NKG2D) ligands on glioma cells in vitro and xenografted in vivo . Specifically suboptimal doses of iPA (0.1 and 1 µM) control the selective upregulation of UL16‐binding protein 2 on p53wt‐expressing U343MG and that of MICA/B on p53mut‐expressing U251MG cells. This event made the glioblastoma cells a potent target for NK cell‐mediated recognition through a NKG2D restricted mechanism. p53 siRNA‐mediated knock‐down and pharmacological inhibition (pifithrin‐α), profoundly prevented the iPA action in restoring the immunogenicity of U343MG cells through a mechanism that is dependent upon p53 status of malignancy. Furthermore, accordingly to the preferential recognition of senescent cells by NK cells, we found that iPA treatment was critical for glioma cells entry in premature senescence through the induction of S and G2/M phase arrest. Collectively, our results indicate that behind the well established cytotoxic and antiangiogenic effects, iPA can also display an immune‐mediated antitumor activity. The indirect engagement of the innate immune system and its additional activity in primary derived patient's glioma cell model (GBM17 and GBM37), fully increase its translational relevance and led to the exploitation of the isoprenoid pathway for a valid therapeutic intervention in antiglioma research. Abstract : What's new? Glioblastomas, due to their high frequency of molecular variations, are largely unaffected by standard anticancer therapies. The tumors, however, are potentially vulnerable to immune‐mediated tumor inhibition. Here, N6‐isopentenyladenosine (iPA), a modified nucleoside that promotes activation of human natural killer (NK) cells, was investigated for its effects on glioblastoma. In human glioma cells and in a glioma mouse model, iPA treatment improved glioma cell immunorecognition via upregulation of NK cell activating receptor NKG2D ligands, leading to senescent tumor cell populations. The findings show that tumor cells can be rendered immunovisible, helping to engage the immune system against glioma growth.